Preventive role of propolis against hyperglycemia and hyperlipidemia in Sprague dawley rats (Rattus norvegicus) animal modelling system - Shahbaz, Muhammad; Arshad, Rizwan; Zahoor, Tahir; Liaqat, Atif; Qaisrani, Tahira Batool; Rafiq, Saima; Javed, Muhammad Sameem; Raza, Nighat; Murtaza, Shamas; Farooq, Umar; Imran, Muhammad; El-Ghorab, Ahmed; et al. (Cellular and Molecular Biology, 2021)
Human diets with functional ingredients showed promising role in management of diseases of modern age like hyperglycemia and hyperlipidemia and even cancer. The study designed to elucidate role of honeybee propolis for management of hyperglycemia and hyperlipidemia states through animal modeling system. Hydroalcoholic extract of propolis was used for development of functional drink with standard recipe and addition of specified dose of extracts (400mg/500mL). Animals were grouped into three studies including study-I fed on regular diet, study-II fed on sucrose enrich diet and study-III fed on diet enriched with cholesterol and monitored to evaluate the results. Various parameters like feed consumption, liquid intake of animals measured regularly whereas body weight recorded at the end of each week of study. At the end of the study animals were analyzed for different blood indicators like blood lipid indices (cholesterol, LDL, HDL concentration and triglyceride contents)), glucose concentration and insulin contents as well. The maximum feed and drink intake were examined in animals, fed with control diet whereas a non substantial mode of intake was recorded in rest of two groups of animals. The consumption of honeybee propolis based drink reduced cholesterol (6.63% to 10.25%) and LDL (9.96% to 11.23%), whilst a sharp increase in HDL level was ranged as 4.12 to 4.49% among animal groups fed with high cholesterol and high sucrose diet. Blood glucose level was decreased by 10.25% and 6.98% however 6.99% and 4.51% increase were observed in plasma insulin level in both studies, study-II and study-III correspondingly. The overall findings of the study showed that drinks prepared using propolis of propolis found effective for management of hyperglycemia and hypercholesterolemia in present animal modelling system.